RI 9438 - Effectiveness of Iron-Based Fuel Additives for Diesel Soot Control - H. William Zeller; T. E. Westpha1 (The National Institute for Occupational Safety and Health (NIOSH), 1992)
The U.S. Bureau of Mimes evaluated the effects of two iron-based fuel additives on diesel particulate matter (DPM) emissions. The 5.6-L, six-cylinder test engine is typical of engines used in underground mines. One additive, ferrous picrate, did not measurably affect exhaust emissions. This report is mainly about a ferrocene-based additive that reduced DPM between 4 and 45 pct, depending on engine operating conditions. The report concludes that the DPM reductions were caused by the catalytic oxidation properties of a ferric oxide coating that developed inside the engine's combustion chamber. The ferric oxide coating also decreased gas-phase hydrocarbons and O, but it increased CO, and NO,. The increase in NO,, of about 12 pct, is considered the only adverse effect of the ferrocene-based fuel additive. The results suggest that the effectiveness of ferrocene was partially offset by increased sulfates because of the high-sulfur fuel used. Recommendations for continuing fuel additive research are presented.